Tuning electrical properties of PZT film deposited by Pulsed Laser Deposition. Issue 8 (1st June 2017) - Gatabi, Javad R.; Rahman, Shafiqur; Amaro, Ana; Nash, Taylor; Rojas-Ramirez, Juan; Pandey, R.K.; Droopad, Ravi
Abstract: The variation of the chemical composition and properties of PZT films as a function of oxygen pressure and laser fluence during pulsed laser deposition is used to tune the electrical properties of the PZT thin films. It is found that the deposition using a 248 nm laser fluence of 1.7 J/cm 2 and an oxygen pressure of 400 mtorr results the PZT films very similar to that of target material. Changing the laser fluences or oxygen pressure, affects the lead content of the deposited film. In the range of oxygen pressure 50–200 mtorr, the Zr/Zr+Ti and Ti/Zr+Ti ratio varies with oxygen pressure while the Pb/Zr+Ti ratio is almost uniform. Using oxygen pressure as a control parameter to tune the chemical compound and electrical properties of the deposited PZT films, the remnant polarization of the PZT films is tuned in the range of 6.6–42.2 µC/cm 2, the dielectric constant is controlled in the range of 29–130, and the piezoelectric constant d33 is controlled in the range of 3.82–4.96 pm/V for a 40 nm thick PZT film.